(untitled) (Submission and Review of Research -Biological Sciences Series, 2025)
This research was conducted in the laboratories of the Plant Biology Department at the Faculty of Science at the University of Lattakia (2023). Two species of Vicia plants (Vicia sativa, Vicia hybrida) were exposed to three different light intensities (strong light: 50,000 lux, medium light: 30,000 lux, weak light: 3000 lux). With alternating lighting period (14 hours light/10 hours darkness). The research aimed to study the effect of different light intensities on the sugar content and plant height of both types studied. It was observed that the amount of sugars clearly varied in the vegetative parts of both species with increasing light intensity, as the sugar content in V. sativa increased with increasing light intensities, while this content decreased in V. hybrida under the influence of high light intensities. A slight decrease in plant height rates was observed in both species with increasing light intensity, and the decrease in plant height in high light was more pronounced in V.hybrida. The results indicate that the two studied traits are differentially affected by the different light intensities of the two types of Vicia plants, and that the V. sativa type is more tolerant to high light intensities in terms of productivity, sugar content, and plant height than the V. hybrida type. The sugar content trait is the most important trait in terms of photosynthesis and productivity, while the plant height remains less important in terms of yield and plant productivity. Based on the above, the results indicate that the V. sativa type of plant is the most suitable for growth and productivity in areas with high light intensities.